Pengaruh Perceived Usefulness Terhadap Behavioral Intention To Use Aplikasi Gojek Dengan Attitude Towards Using Sebagai Variabel Intervening Pada Pengguna Layanan Aplikasi Gojek Di Kota Padang - Mulyaa, Suci; Mulyati, Yofina (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This research aims to determine the effect of perceived usefulness on behavioral intention to use the Gojek application with attitude towards using as an intervening variable among Gojek application service users in the city of Padang. The population in this study is all users of the Gojek application service in the city of Padang, the exact number of which is unknown with a sample size of 246 people. The sampling technique uses a purposive sampling method. The data analysis used is SEM-Partial Least Square (PLS). Based on the results of this research, the results obtained are summarized as follows: 1) Perceived usefulness has a positive and significant effect on attitude towards using the Gojek application. 2) Perceived usefulness has a positive and significant effect on behavioral intention to use the Gojek application. 3) Attitude towards using has a positive and significant effect on behavioral intention to use the Gojek application. 4) Perceived usefulness has a positive and significant effect on behavioral intention to use the Gojek application with attitude towards using as an intervening variable.